2021
DOI: 10.3390/ijerph18116156
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Consistent Association between Asthma, Allergic Diseases, and Intestinal Helminth Infection in School-Aged Children in the Province of Bengo, Angola

Abstract: Epidemiological studies have shown conflicting findings on the relationship between asthma, atopy, and intestinal helminth infections. There are no such studies from Angola; therefore, we aimed to evaluate the relationship between asthma, allergic diseases, atopy, and intestinal helminth infection in Angolan schoolchildren. We performed a cross-sectional study of schoolchildren between September and November 2017. Five schools (three urban, two rural) were randomly selected. Asthma, rhinoconjunctivitis, and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
1
1
Order By: Relevance
“…There was no significant association between EE and current ESs and the participants’ sex ( p > 0.005). Our findings were consistent with the ISAAC cross-sectional study, which included children aged 6 to 7 years in Angola and reported no association between sex and AE symptoms [ 57 ]. It is uncertain whether gender or sex makes young children more susceptible to eczema symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no significant association between EE and current ESs and the participants’ sex ( p > 0.005). Our findings were consistent with the ISAAC cross-sectional study, which included children aged 6 to 7 years in Angola and reported no association between sex and AE symptoms [ 57 ]. It is uncertain whether gender or sex makes young children more susceptible to eczema symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the overall prevalence of EE (11.9%) and current ESs (13.37%) was found to be lower than in other studies conducted in Africa, such as Angola, where EE was reported at 18.4% among 6-to 7-year-old children (Ref. [57]) and Ethiopia, where AE was reported at 21% among children under 12 years old [58]. It is worth noting that South Africa has a larger economy than Angola and Ethiopia [59], with the highest consumption of coal on the African continent in 2023.…”
Section: Discussioncontrasting
confidence: 74%
“…It is important to note that unrelated factors such as allergic reactions, dermatitis, and insect bites among others can contribute to skin itching. A study by Arrais et al 29 among Angolan school‐aged children has found no significant association between skin infection and intestinal helminthic infections.…”
Section: Discussionmentioning
confidence: 93%